Increases in CD4+ T-Cell Count at Antiretroviral Therapy Initiation among HIV-Positive Illicit Drug users during a Treatment-as-Prevention Initiative in Canada. Issue 5 (July 2017) - Tran, Mimi; Wood, Evan; Kerr, Thomas; Patterson, Sophie; Bangsberg, David; Dong, Huiru; Guillemi, Silvia; Montaner, Julio SG; Milloy, M-J
Background: Although treatment-as-prevention (TasP) efforts are a new cornerstone of efforts to respond to the HIV/AIDS pandemic, their effects among people who use drugs (PWUD) have not been fully evaluated. This study characterizes temporal trends in CD4 + T-cell (CD4) count at ART initiation and rates of virological response among HIV-positive PWUD during a TasP initiative. Methods: We used data on individuals initiating ART within a prospective cohort of PWUD linked to comprehensive clinical records. Using multivariable linear regression, we evaluated the relationship between CD4 count prior to ART initiation and year of initiation and time to HIV-1 RNA viral load <50 copies/ml following initiation using Cox proportional hazards modelling. Results: Among 355 individuals, CD4 count at initiation rose from 130 to 330 cells/ml from 2005 to 2013. In multivariable regression, initiation year was significantly associated with higher CD4 count (β=29.5 cells per year, 95% CI 21.0, 37.9). Initiating ART at higher CD4 counts was significantly associated with optimal viral response (adjusted hazard ratio =1.13 per 100 cells/ml increase, 95% CI 1.05, 1.22). Conclusions: Increases in CD4 cell count at initiation over time was associated with superior virological response, consistent with the aims of the TasP initiative.